Limited-Angle X-ray Luminescence Tomography: Methodology and Feasibility Study - Carpenter, CM (2011)
X-ray Luminescence Tomography (XLT) has recently been proposed as a new imaging modality for biological imaging applications. This modality utilizes phosphor nanoparticles which luminesce near-infrared light when excited by X-ray photons. The advantages of this modality are that it uniquely combines high sensitivity of radioluminescent nanoparticles and high spatial localization of collimated X-ray beams. Currently, XLT has been demonstrated using X-ray spatial encoding to resolve the imaging volume. However, there are applications where the X-ray excitation may be limited by geometry, where increased temporal resolution is desired, or where a lower dose is mandatory. This paper extends the utility of XLT to meet these requirements by incorporating a photon propagation model into the reconstruction algorithm to recover dimensions remaining in an X-ray limited angle (LA) geometry. This enables such applications as image-guided surgery, where the ability to resolve lesions at depths of several centimeters can be the key to successful resection. The hybrid X-ray/diffuse optical model is first formulated and then demonstrated in a breast-sized phantom, simulating a breast lumpectomy geometry. Both numerical and experimental phantoms are tested, with lesion-simulating objects of various sizes and depths. Results show localization accuracy with median error of 2.2mm, or 4% of object depth, for small 2–14mm-diameter lesions positioned from 1cm to 4.5cm in depth. This compares favorably with fluorescence optical imaging, which is not able to resolve such small objects at this depth. The recovered lesion size has lower size-bias in the X-ray excitation direction than the optical direction, which is expected due to the increased optical scatter. However, the technique is shown to be quite invariant in recovered size with respect to depth, as the standard deviation is less than 2.5mm. Sensitivity is a function of dose; radiological doses are found to provide sufficient recovery for μg/ml concentrations, while therapy dosages provide recovery for ng/ml concentrations. Experimental phantom results agree closely with the numerical results, with positional errors recovered within 8.6% of the effective depth for a 5mm object, and within 5.2% of the depth for a 10mm object. Object size median error is within 2.3% and 2% for the 5mm and 10mm objects, respectively. For shallow-to-medium depth applications where optical and radio-emission imaging modalities are not ideal, such as in intra-operative procedures, LAXLT may be a useful tool to detect molecular signatures of disease.